A Comprehensive Review on Microbubble Concept, Development and Its Application in Therapeutic Drug Delivery and Clinical Management of Disease - Rathor S.; Aamir S.; Bhatt D.C.; Kumar K.; Kumar V. (My University, 2025)
BACKGROUND: The general purpose of this review was to briefly describe the Gastro-Retentive Drug Delivery System (GRDDS) and to primarily focus on mechanisms of flotation for gastric retention. METHODS: The principle mechanism of Floating Drug Delivery Systems (FDDS) is mainly based on hydro-dynamically controlled low-density system, which gets swollen when comes in contact with the gastric environment and remains buoyant for an extended period of time with improved bioavailability and therapeutic efficacy. The main perspective of this review was to focus on microbubble drug delivery due to its wide range of applications. RESULTS: Microbubble is a new, economically viable, and non-invasive technique that is alternative to conventional techniques. The size of microbubbles ranges from 1-100 micrometers, which contain oxygen or air and remain suspended for prolonged drug release. Due to its great potential, microbubble is used in the therapeutic delivery of drug molecules or genetic material at their specific targeted site in various diseases. The recent research also suggests that ultrasound-mediated microbubble is more frequently used in the biomedical field for imaging of site-specific molecule targeting for the detection of disease and site-specific drug delivery. CONCLUSION: Gastro-retentive floating drug delivery system was considered as the most favorable approach for site-specific drug delivery. But nowadays, microbubble is gaining more popularity for its potential applications in the biomedical field. In recent years, there is much progress in microbubble for site-specific delivery of a drug or genetic material. Recent research also suggests that the ultrasound- mediated microbubble has shown a positive impact on the diagnosis and clinical management of various diseases such as liver cirrhosis, brain tumor, ocular, and urinary tract infection. Copyright© Bentham Science Publishers; For any queries, please email at epub@benthamscience.net.